2007
DOI: 10.1038/modpathol.3800830
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of the basal type and HER-2/neu type in brain metastasis from breast cancer

Abstract: Although breast cancer is the second most common cause of central nervous system (CNS) metastases with a notable increase of incidence, only few studies on brain-metastasizing breast cancer are available. In this immunohistochemical and fluorescence in situ hybridization (FISH) study, metastases to the CNS (n ¼ 85) and primary breast cancers, with known involvement of the CNS (n ¼ 44) including paired primary and metastasized tumours (n ¼ 23), were investigated retrospectively for the expression of oestrogen-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 35 publications
4
98
2
2
Order By: Relevance
“…Taken together, 35% of the whole cohort reported boneonly metastasis at the start of treatment, which is consistent with the literature naming a proportion of 17e37% [11,24]. In contrast, HER2-positive tumours are more likely to metastasise to the brain during the course of disease, with an incidence of 25e34% [2,25,26]. Consistent with these results, the frequency of brain metastases in the HER2-positive setting was 31% during the course of disease in our cohort (data on file).…”
Section: Discussionsupporting
confidence: 86%
“…Taken together, 35% of the whole cohort reported boneonly metastasis at the start of treatment, which is consistent with the literature naming a proportion of 17e37% [11,24]. In contrast, HER2-positive tumours are more likely to metastasise to the brain during the course of disease, with an incidence of 25e34% [2,25,26]. Consistent with these results, the frequency of brain metastases in the HER2-positive setting was 31% during the course of disease in our cohort (data on file).…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, the BRCA1 pathway seems to be altered in sporadic breast cancers with a 'basal' phenotype. 38 The trend of basal-like cancers to metastasise to brain, 39,40 which was also shown in patients with BRCA1 mutations, is also noteworthy. 41 Can pathology aid clinical decision making?…”
Section: 2829mentioning
confidence: 98%
“…CNS or brain metastases traditionally occur in 10-16% of metastatic breast cancer patients and are associated with a dismal prognosis. In a recent study, Gaedcke et al [115] found that the majority of breast cancer that developed CNS metastases are BLC and HER2 positive. These CNS metastatic tumours are usually hormone receptor negative, EGFR and basal CKs (CK5/14) positive [116,117].…”
Section: Metastatic Patternmentioning
confidence: 99%